KEKUATAN HUKUM HASIL TEKS DEOXYRIBONUCLEIC ACID (DNA) TERHADAP STATUS ANAK LUAR KAWIN YANG TIDAK DIAKUI OLEH AYAH BIOLOGISNYA PASCA PUTUSAN MAHKAMAH KONSTITUSI NO.46/PUU-VIII/2010 - CINTHIA FEBRILLA RAMADHANI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Hasim Purba, SH, MHum2. Dr. Rosnidar Sembiring, SH, Mhum3. Dr. T. Keizerina Devi A, SH, CN, Mhum DNA ( Deoxyribonucleic acid) test is used to find out some information about one's genetics in order to find out his heredity and his risk for a certain illness so that the similarity of genetics between a father and his illegitimate children. The Constitutional Court's Ruling No. 46/PUU-VIII/2010 states that DNA test can be used as valid evidencein the case of an illegitimate child's lineage versus his biological father. The result of the research shows that evidence cannot stand by itself; it has to be supported by witness testimones which say that the child's parents have been married although the marriage does not meet the requirements for its legitimacyKeywords: DNA test, Illegitimate Child, Biological Father